2018
DOI: 10.1007/s10689-018-0091-5
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol profile in women with premature menopause after risk reducing salpingo-oophorectomy

Abstract: This cross-sectional study aimed to investigate the effect of premenopausal risk reducing salpingo-oophorectomy (RRSO) on the cholesterol profile of women at increased ovarian cancer risk and to assess possible effects of age at and time since RRSO. We included 207 women who underwent RRSO before menopausal age (52 years) attending the family cancer clinic of an academic hospital and 828 age-matched women from a general population cohort (PREVEND). Participants filled out a questionnaire on socio-demographic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Women with an early natural menopause (<40 years) are at higher risk of developing CVD, and they have a higher CVD mortality than age-matched peers [ 23 - 26 ]. However, it has been debated whether this association is causal, and it has been speculated that this might also be explained by early vascular aging predisposing to both POI and cardiovascular disease [ 30 , 81 ]. If this is true, an artificial early menopause might not be associated with increased CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Women with an early natural menopause (<40 years) are at higher risk of developing CVD, and they have a higher CVD mortality than age-matched peers [ 23 - 26 ]. However, it has been debated whether this association is causal, and it has been speculated that this might also be explained by early vascular aging predisposing to both POI and cardiovascular disease [ 30 , 81 ]. If this is true, an artificial early menopause might not be associated with increased CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen hormone has a protective effect on blood vessel walls and the composition of LDL and HDL cholesterol, maintaining the elasticity of blood vessels, including the blood vessels of the heart (Jati, 2022). The causes of increased cholesterol levels in menopausal women besides the decrease in estrogen hormones are overweight, lack of active movement and unhealthy habits (Teixeira et al, 2019).…”
Section: Univariate Analysismentioning
confidence: 99%
“…Two small follow-up studies in women with artificial menopause after bilateral oophorectomy observed an elevation in LDL cholesterol in these women. 34,35 A follow-up study of women previously diagnosed with POI (n ¼ 80) in the second assessment at the age of more than 45 years identified an unfavorable cardiovascular risk profile, including elevated chronic inflammatory factors, more abdominal fat, and a trend toward increased hypertension, as well as impaired kidney function. 36 However, no signs of increased subclinical atherosclerosis in women with POI were found.…”
Section: Cardiovascular Risk Factors As Predictors In Women With Premature Menopausementioning
confidence: 99%